Nudge/behavioural-based interventions for reducing polythene bag usage: A case study - Dolly Jamwal; Rupali Satsangi (Acta Psychologica, 2025)
The main aim of the study is to assess the effectiveness of combined nudge and behavioural-based interventions in encouraging the adoption of sustainable consumption behaviour, specifically the use of polythene bags in Indian society. The study identifies a gap in the literature related to the combined impact of these two types of interventions. The study implemented three interventions: A nudge poster designed to target System 1 thinking through social norms and visual cues, and two behavioural interventions, The Plastic Tree Intervention and The Eating Plastic Intervention, designed to influence System 2 thinking by stimulating reflective cognition.The study found a significant 32.11 % reduction in polythene bag usage and a 20.93 % increase in the adoption of sustainable bags. A major derivation is the significance of combining nudge and behavioural interventions which can be used for future sustainable consumption initiatives. The results indicate that integrated interventions may be more effective, time-efficient, and economical compared to individual intervention types. Future research is intended to conduct longitudinal studies, develop multi-level interventions, and design interventions that address most felt behavioural barriers to sustainable bag use identified in the study, such as limited availability, convenience, and cost.